Commentary on 'Social skills groups for people aged 6 to 21 with autism spectrum disorders (ASD)'. Issue 2 (7th March 2013) - Gillies, Donna; Carroll, Louisa; Loos, Melissa
Abstract This is a commentary on a Cochrane review, published in this issue of EBCH, first published as: Reichow B, Steiner AM, Volkmar F. Social skills groups for people aged 6 to 21 with autism spectrum disorders (ASD). Cochrane Database of Systematic Reviews 2012, Issue 7. Art. No.: CD008511. DOI: 10.1002/14651858.CD008511.pub2. Further information for this Cochrane review is available in this issue of EBCH in the accompanying Summary article.